Variation Factors of Some Trace Elements (Selenium, Copper and Zinc) and Enzymes Indicators of Muscular Fatigue in the Serum of Camels (Camelus dromedarius) in the United Arab Emirates - R. Seboussi; B. Faye; G. Alhadrami (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2004)
The authors investigated the effects of age, sex, breed and physiological status on selenium (Se), copper (Cu), zinc (Zn), creatine-kinase (CPK), alanine aminotransferase (ALT) and aspartate aminotransferase in the dromedary (Camelus dromedarius). A total of 240 apparently healthy animals, of which 166 were of the local breed, 68 crossbred, and 6 Sudanese, were randomly selected within a camel population originating from the same herd. The camels were divided into age groups: 2-4 years old, 5-7 years old, and 8 years or older. The camels were fed on alfalfa, a lentil mixture, dates and soya beans, in addition to a concentrate. The study revealed no effect of the breed on measured parameters. The lower Zn level found might have been due to lower Zn contents in the supplemented feed. Significant correlations were obtained between Se and Cu (0.292; P < 0.01), Se and Zn (– 0.0283; P < 0.01). Sex showed a high significant influence on the measured variables, with the exception of ALT. The physiological status influenced all measures, but not CPK. There is a need to integrate these elements and define their precise role in the racing camel.